2019
DOI: 10.5217/ir.2018.00103
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of cold forceps polypectomy utilizing the jumbo cup: a prospective study

Abstract: Background/Aims There are few prospective studies on cold forceps polypectomy (CFP) using jumbo cup forceps. Therefore, we examined patients with diminutive polyps (5 mm or smaller) treated with CFP using jumbo cup forceps to achieve an adenoma-free colon and also assessed the safety of the procedure and the recurrence rate of missed or residual polyp after CFP by performing follow-up colonoscopy 1 year later. Methods We included patients with up to 5 adenomas removed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In this study, we used standard-size forceps to assess the risk of duodenal perforation. However, data on outcomes with CFP for colorectal adenoma using jumbo forceps are favorable [9] suggest that perforation of the digestive tract may not be a consideration with use of large forceps. However, the efficacy of use of jumbo biopsy forceps should be verified, given the potential to further shorten procedure time and number of biopsies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we used standard-size forceps to assess the risk of duodenal perforation. However, data on outcomes with CFP for colorectal adenoma using jumbo forceps are favorable [9] suggest that perforation of the digestive tract may not be a consideration with use of large forceps. However, the efficacy of use of jumbo biopsy forceps should be verified, given the potential to further shorten procedure time and number of biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…There have been some reports about the efficacy and safety of cold forceps polypectomy (CFP) and cold snare polypectomy (CSP) for diminutive colorectal polyps 9 10 11 12 13 14 . A single study revealed the safety and effectiveness of cold polypectomy for NADA 15 ; however, most of the patients in that study underwent CSP, and there are no clear data about CFP.…”
Section: Introductionmentioning
confidence: 99%
“…Although the study was rather limited, the data is concerning regarding complete polyp resection by simply using biopsy forceps [ 13 ]. On the other hand, in a more recent study from 2019, Hasegawa et al assessed the resection of diminutive polyps using jumbo cup forceps in a larger study with 361 patients and 573 adenomas and concluded that this technique was safe for complete one-bite resections [ 14 ].…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…Delayed PPB was defined as the presentation of melena or hematochezia within 30 days of the colonoscopic procedure, with the symptoms requiring hospitalization or a hemostasis procedure. 21 , 22 Clinical outcomes related to PPB following the colonoscopic removal of colorectal polyps, including need for colonoscopic hemostasis, surgical intervention, and mortality, were also evaluated.…”
Section: Methodsmentioning
confidence: 99%